2017
DOI: 10.1091/mbc.e17-01-0064
|View full text |Cite
|
Sign up to set email alerts
|

Retinoschisin is linked to retinal Na/K-ATPase signaling and localization

Abstract: Retinoschisin binds to the extracellular domain of Na/K-ATPase subunit β2. Retinoschisin inhibits Na/K-ATPase–associated signaling cascades and affects Na/K-ATPase localization. The retinoschisin-Na/K-ATPase complex overlaps with signaling mediators. Defective Na/K-ATPase signaling by retinoschisin deficiency may promote retinal dystrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(59 citation statements)
references
References 73 publications
4
55
0
Order By: Relevance
“…These defects were observed at a frequency of roughly 4% relative to the total rod photoreceptor population. To further examine these defects, we stained IS membrane with Na/K ATPase (23,24) and OS with rhodopsin. MPC KO retinas formed small vacuoles in the IS and IS-OS junction ( Fig.…”
Section: Mpc-deficient Retinas Have Distinctive Ultrastructural Defectsmentioning
confidence: 99%
“…These defects were observed at a frequency of roughly 4% relative to the total rod photoreceptor population. To further examine these defects, we stained IS membrane with Na/K ATPase (23,24) and OS with rhodopsin. MPC KO retinas formed small vacuoles in the IS and IS-OS junction ( Fig.…”
Section: Mpc-deficient Retinas Have Distinctive Ultrastructural Defectsmentioning
confidence: 99%
“…20,21 Page 4 of 33 Recent studies showed that RS1 regulates Erk signaling and apoptosis in retinal cells while also exerting regulatory effects on Na + /K + -ATPase signaling and localization. 22,23 Despite advances in understanding XLRS pathophysiology, 6,15,24,25 the factors underlying the heterogeneity of clinical phenotypes in terms of disease onset, symptoms, severity, and progression, as seen even between family members have not been entirely clear.…”
Section: Introductionmentioning
confidence: 99%
“…Retinoschisin, a 224 amino acid protein, is secreted from photoreceptors and bipolar cells in retina and has been shown to be crucial for cell adhesion during retinal development [ 18 ]. It has been suggested that retinoschisin may also be involved in mitogen-activated protein kinase signaling and apoptosis in retina [ 18 ] and recently has been shown to influence Na/K-ATPase signaling and localization [ 19 ]. Employing cryo-electron microscopy, it has been discovered that functional retinoschisin forms a dimer of octamer rings comprising a hexadecamer.…”
Section: Introductionmentioning
confidence: 99%